94 Real-world use of sacubitril-valsartan in the south of England. (17th July 2020) - Dimarco, Anthony; Haydock, Paul; Flett, Andrew; Cowburn, Peter; Chandrasekaran, Badrinathan; Foley, Paul; Dixon, Giles; Jackson, Thomas; Critoph, Chris; Davis, Hannah; Kelly, Dominic
Abstract : Background: The landmark PARADIGM-HF trial discovered that use of the angiotensin-receptor-neprolysin inhibitor sacubitril-valsartan (Sac-Val) led to significant reductions in mortality and heart failure hospitalisation. The inclusion criteria specified adults on a stable dose of angiotensin converting enzyme inhibitor (ACEi)/angiotensin receptor blocker (ARB) with NHYA class II-IV heart failure, left ventricular ejection fraction (LVEF) <35% and elevated B-type natriuretic peptide concentration. Patients were excluded if they had symptomatic hypotension, systolic blood pressure (SBP) <100mmHg, serum potassium >5.2mmol/L at screening, eGFR <30ml/min/1.73m2, or previous angioedema/side effects caused by ACEi/ARB. The ESC guideline for the management of acute and chronic heart failure recommends use of Sac-Val in ambulatory patients who are symptomatic despite optimal medical therapy and fulfil the PARADIGM-HF trial inclusion criteria. In the UK, NICE has published similar recommendations. Purpose: Our aim was to investigate the extent to which the real-world (clinic) use of Sac-Val mirrors that of the PARADIGM-HF population and complies with guideline recommendations. Methods: We retrospectively analysed records of patients started on Sac-Val between 2017-2019 at four centres in the South of England. Data from initial screening to last available were included. We compared the results from clinic patients to those in the treatment arm of the PARADIGM-HF study. A total of 552 patient records were reviewed. Results: 438 patients were included in the final analysis. Our cohort was comparable in age and gender to the trial population (table 1 ). Similar proportions were NYHA class III but more clinic patients were class I or IV (figure 1 ). Baseline mean SBP, creatinine, and LVEF were almost identical. Our patient group had less hypertension and diabetes, and significantly fewer had been admitted previously with heart failure (62.3% vs 18.5%, p<0.001). History of atrial fibrillation was not significantly different (PARADIGH-HF 36.2% vs Clinic 37.9%, p0.48). More clinic patients had implanted cardiac devices (43.8% vs 14.9% [p<0.001] for ICD and 34.7% vs 7% [p<0.001] for CRT). 92.5% of clinic patients had no exclusion criteria - 4 had an eGFR <30ml/min/1.73m2 at baseline and 30 had an SBP<100mmHg. 74% fulfilled inclusion criteria, 68 were NYHA class I; 47 had an LVEF ≥35%. Fewer clinic patients discontinued Sac-Val (13.9% vs. 17.8%, p0.04 – table 2 ). The most common reasons given were hypotension (n=8), dizziness (n=7), and hyperkalaemia (n=5). 33 clinic patients died (7.5%) compared to 558 (13.3%) of those in the PARADIGM-HF cohort (p0.04). A higher proportion of patients in the clinic group experienced a decline in eGFR compared to the study cohort, and a greater proportion of patients treated with Sac-Val in the clinic group had a creatinine >3.0mg/dl during follow up. Conclusion: We found that (a) baseline characteristics of our clinic HF population are broadly similar to those treated in the PARADIGM-HF study, (b) Cardiologists from England have prescribed Sac-Val in a wide range of HF patients (c) Sac-Val is better tolerated than the trial data suggested. Conflict of Interest: None